The Hollow - Roberts, Nora. (New York : Jove Books, 2008)
"For Fox, Caleb, Gage and the other residents of Hawkins Hollow, the number seven portends doom--ever since, as boys, they freed a demon trapped for centuries when their blood spilled upon The Pagan Stone. Their innocent bonding ritual led to seven days of madness, every seven years. And now, as the dreaded seventh month looms before them, the men can feel the storm brewing"--from publisher's web site.
Keywords: Telepathy -- Fiction; Spiritual warfare -- Fiction; Occult fiction; Love stories